Effect of Helminth Infestationin Children Infected with Human Immunodeficiency Virus (HIV) - Orji, Maria-Lauretta Chito; Onyire, Nnamdi Benson; Ibe, Bede C.; Ibekwe, Roland (Journal of Nepal Paediatric Society, 2017)
Introduction: Infection by human immunodeficiency virus results in immune destruction, while studies among the Ethiopian immigrants in Israel showed that chronic helminthiasis induces immune dysregulation. With destruction of CD4+ cell and consequently progression to AIDS, the host may be more susceptible to invading organisms such as helminths. This study was aimed at determining the effect of immune state on the prevalence and intensity of helminth infection in HIV infected children in two hospitals in Abakaliki. Material and Methods: It was a cross sectional study that involved consecutive recruitment of 84 confirmed HIV infected children attending the ART clinic. Stool analysis for subjects was done, using the Kato-Katz technique. Blood sample for estimation of CD4 cell count was carried outusing flow cytometer from the HIV positive subjects. Results: A total of 84 subjects were recruited during the study period, majority were males (58.3%). Male to female ratio was 1.4:1. The age range of participants was 2-17 years, while mean age of subjects infected with helminthiasis was 6.10± 3.34 year. A significant number of subjects in advanced and severe immunological stages had helminthiasis (χ2 =12.49, p=0.001). There was however no significant relationship between intensity of helminthiasis and immunologic stages of subjects. Conclusion: The study suggests that immunodeficiency state may increase the susceptibility of helminth infection in HIV infected children. Hence children with HIV/AIDS may benefit from routine testing and/or de-worming of helminth infection.